Synthesis of Tripodal and Hexapodal Pyrazole- and Benzimidazole-Bearing Compounds - Koch, Niklas; Mazik, Monika (Synthesis, 2013)
The syntheses of eight new tripodal and hexapodal benzimidazole- and pyrazole-bearing compounds, which are all potentially applicable for use as artificial receptors, are described. The prepared compounds contain either bromo-substituted heteroaromatic rings, able to participate in halogen-bonding interactions, or their analogues lacking the bromo substituents. Furthermore, the preparation of a new trisbenzimidazolium cage is included in this work. All used practical synthetic procedures are facilely accomplishable and provide the products in good to excellent yields. In addition, slightly modified, simplified synthetic procedures for five known tripodal compounds, which lead to better yields than those previously reported, are also detailed.
Keywords: triethylbenzene scaffold; trimethoxybenzene scaffold; tripodal receptors; hexapodal receptors; cyclophanes